FORMATION OF CONSUMER LOYALTY IN ENTERPRISE DIGITAL MARKETING: A BEHAVIORAL AND ECONOMIC APPROACH - MILCHEVA, Viktoriia; YEVTUSHEVSKA, Olha; ANTONYUK, Yulia; MATUZNYI, Oleksii; KORIAHIN, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Modern enterprises and their clients are increasingly integrating digital technologies into all aspects of their activities, which not only generates new opportunities for optimizing interaction and business development but also stimulates innovative potential. The purpose of this study is to identify the specific features of consumer loyalty formation in digital marketing within enterprises, within the framework of both behavioural and economic approaches, under current conditions.Given the rapid proliferation of digital tools in marketing, the study highlights, from a practical perspective, the contemporary challenges and trends that manifest in ensuring consumer loyalty. It has been established that customer loyalty has traditionally been considered a key factor in driving extensive growth, focusing on expanding the client base by attracting new customers. Particular attention is paid to the comparative analysis of Ukrainian and international practices in shaping consumer loyalty in enterprise digital marketing. The findings reveal that the Ukrainian practice of consumer loyalty formation in digital marketing is predominantly focused on stimulating demand in the short term and fostering emotional contact with consumers. As a standard feature, the active use of digital channels and gamification has been identified, while the distinction lies in the scale and depth of implementation.It has been demonstrated that the approach to customer loyalty can be based on two core enterprise strategies: expansion (marketing management of loyalty focused on meeting the expectations of potential customers) and retention (marketing support of existing customer loyalty aimed at preventing their attrition). Furthermore, the study substantiates the effectiveness and prospects of modern approaches to training enterprise personnel engaged in marketing activities, particularly those based on gamification.
Keywords: consumer loyalty; digital marketing; consumer behavior; competitiveness; marketing strategy; risk